Changes in trends and patterns of glycaemic control at Ghana's National Diabetes Management and Research Centre during the era of the COVID-19 pandemic. - Swithin Mustapha Swaray; John Tetteh; Sampson Kafui Djonor; George Ekem-Ferguson; Ruth Yawa Clottey; Atiase Yacoba; Alfred Edwin Yawson (Public Library of Science (PLoS), 2023)
Background Maintaining optimal glycaemic control (GC) delays the onset and progression of diabetes-related complications, especially microvascular complications. We aimed to establish the trend and pattern of GC, and its associated factors in persons living with diabetes (PLWD), and to examine the influence of COVID-19 on GC. Methods A retrospective study involving secondary data from 2,593 patients' physical records from the National Diabetes Management and Research Centre (NDMRC) in Accra, extracted from 2015-2021. Growth rate of GC was assessed, and ordinal logistic and Poisson models weighted with Mahalanobis distance matching within propensity caliper were adopted to assess the impact of COVID-19 pandemic on GC. Stata 16.1 was utilized and the significant value set as p≤0.05. Results GC pattern indicated a steady deterioration ranging from 38.6% (95%CI = 34.5-42.9) in 2015 to 69.2% (95%CI = 63.5-74.4) in 2021. The overall growth from 2015-2021 was 8.7%. Being a woman and increasing diastolic pressure significantly increase the likelihood of poor glycaemic control (PGC) by 22% and 25%, respectively compared with their respective counterparts [aOR(95%CI = 1.01-1.46 and 1.25(1.10-1.41), respectively]; whilst lower age increased the risk of PGC throughout the years. We found that risk of PGC during the era of COVID-19 was approximately 1.57(95%CI = 1.08-2.30) times significant, whilst the adjusted prevalence ratio (aPR) of PGC during the era of COVID-19 was approximately 64% significantly higher than the era without COVID-19 (aPR = 1.64, 95%CI = 1.10-2.43). Conclusion GC worsened from 2015-2021, especially during the COVID era. Younger age, uncontrolled blood pressure and/or being a woman were associated with PGC. The NDMRC and other centres that provide specialist healthcare in resource-limited settings, must determine the factors that militate against optimal service delivery in the era of the COVID-19 pandemic, and implement measures that would improve resilience in provision of essential care in the face of shocks.